Hubungan Pola Asuh Dan Tingkat Kepercayaan Diri Dengan Perilaku Bullying Yang Dimediasi Oleh Konformitas pada Siswa Sekolah Menengah Atas (SMA) - Wakhid, Dimas Nur; Winta, Mulya Virgonita I; Erlangga , Erwin (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2026)
Bullying is a conscious act that causes injury and fear through mental or physical aggression, and is still common among adolescents, both as victims and perpetrators. The aims of this study is to analyze the relationship between parenting styles and self-confidence with bullying behavior mediated by conformity in high school students. The research used a quantitative design with 100 respondents as subjects through total sampling, and data analysis was tested using Partial Least Squares. The findings of this study proved that self-confidence was significantly related to bullying behavior (p = 0.017), while parenting styles, conformity, and the mediating role of conformity were not significant. Theoretically, these findings emphasize the importance of individual factors, especially self-confidence, in influencing adolescent aggressive behavior, while environmental influences or group pressure are not always determinants. Practically, this study suggests strengthening students' self-confidence as a primary strategy for bullying prevention, and provides guidance for teachers and parents to focus on character development and students' self-regulation skills in dealing with social interactions. Keywords:parenting style; self-confidence; conformity; bullying behavior